Financial inclusion in food, land and water systems: what works for women? - Puskur, Ranjitha; Verma, Benu; Elias, Marlene; Mujawamariya, Gaudiose; Haan, Nicoline C. de; Atakos, Vivian (CGIAR Gender Equality and Inclusion, 2025)
This brief draws on distilled evidence from research and practice from CGIAR and beyond to highlight how to design financial products, approaches and processes to reach, benefit and empower women through financial inclusion.